Association of Obesity and Breast Cancer Risk: The Role of Estrogen, Tumor Necrosis Factor-alpha, and Adiponectin as Risk factors (preliminary study) - Ampi Retnowarnadi; Siti Boedina Kresno; Mansyur Arif (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Breast cancer is the most frequent cancer diagnosed among women. Many factors influence the carcinogenesis of breast cancer. The aim of this study to analyze the role of obesity (waist circumference and body mass index), serum Estradiol levels, TNF-α, and Adiponectin in the occurrence of breast cancer.METHODS: This was observational study with casecontrol design. Eleven breast cancer patients as cases and twelve Fibroadenoma Mammae (FAM) patients as controls were analyzed. The serum Estrogen, TNF-α and Adiponectin were examined in their association with breast cancer risk.RESULTS: Women with breast tumor and waist circumference > 80 cm have significantly higher breast cancer risk than women with breast tumor and waist circumference <80 cm (OR 8.75; 95% CI=1.24-61.88; p=0.029). Women with breast tumor and higher serum TNF-α levels (>2.30 pg/ml) have higher breast cancer risk (19.25 times) than women with breast tumor and have lower serum TNF-α levels (95% CI=1.77-209.55, p=0.015). Whereas, women with breast tumor and lower Adiponectin/TNF-α ratio (< 2.13) have higher breast cancer risk (22.5 times) than women with breast tumor and higher Adiponectin/TNF-α (95% CI=2.60-194.51; p=0.005).CONCLUSION: These results suggest that high concentration of serum TNF-α, waist circumference >80 cm and low Adiponectin/TNF-α ratio in women with breast tumor are significantly associated with an increased risk for breast cancer.KEYWORDS: Obesity, breast cancer, adiponectin/TNF-α ratio